(untitled) (Global Journal of Science Frontier Research, 2012)
Various economical and ecological consequences of the air pollution affect animals, plants, food hygiene and human health. One of the most endangered components of the environment is the air. Elevated anthropogenic SO 2 emissions can also have negative influences upon the human health, environmental conditions, and ecosystems. Monitoring of the air pollution is thus extremely important. The most emissions come from industry, heavy traffic, emissions and population density. Submitted work includes the summary of the sulphur dioxide pollution and its impact on the environment in the area of chemical factory Duslo Šaľa, Inc. Monitoring anthropic impacts helps us to predict what requirements on space particular industry requires and how they act in the area. The basis of our evaluation was observing diversity monitoring and types of negative anthropogenic features in monitored area: concentrations of SO 2 in air, real sources of air pollution from the vehicles and other mechanisms and real sources of air pollution from local town residential area sources.